Transforming Organizational Culture in a State-Owned Construction Firm: Insights from the Competing Values Framework - Kismono, Gugup; Gunawan, Stephen (Ilomata International Journal of Management, 2024)
This study investigated the type of organizational culture in a state-owned construction firm using the Competing Values Framework. Diagnosing the organizational culture is essential to identifying the gap between the current and preferred cultures, and guiding the development of transformation programs. Data was collected from 58 participants using validated and reliable instruments applicable across various industries and countries. Descriptive analysis categorized the organizational culture, revealing a gap between the current and preferred types. The current culture was evenly spread across clan, adhocracy, market, and hierarchy types, whereas the preferred culture leaned towards market culture. To bridge this gap, a transformation program emphasizing transformational leadership and human resources functioning as business partners is necessary. The study faced limitations, including a relatively low response rate, although managerial responses were robust. The use of an ipsative rating scale precluded causal statistical analysis, suggesting future research might benefit from a Likert-type scale for more sophisticated analyses, including individual comparisons. This research provides a practical case of organizational culture transformation, emphasizing the shift towards a market culture in response to industry developments and business competition. Leaders are encouraged to consider individual characteristics, offer personal attention, develop a visionary approach, and communicate purposes with humility. Human resource functions should align HR practices with the company’s strategy and leverage unique employee capabilities. The study highlights the need for an ambidextrous culture and suggests that effective cultural shifts can be achieved through vertical and horizontal alignment.